CRITICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING MATHEMATICS QUESTIONS OF THE NATIONAL SCIENCE COMPETITION - Malinda, Ari; Roza, Yenita; Maimunah, Maimunah (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
Critical thinking ability is the ability to identify problems, evaluate and develop arguments and solve problems appropriately. Critical thinking must be mastered as a fundamental ability that students must possess. One strategy that can develop students' critical thinking skills is giving problem-solving tasks, such as KSN questions. The KSN questions have more complex problems and a very high difficulty level. This study aimed to measure students' critical thinking in solving the problems of the National Science Competition (KSN) in the field of Mathematics. This research is qualitative descriptive research. The research subjects were three 8th-grade students who were members of the competition team of Public Junior high School 3 Siak Kecil. The data collection technique was in the form of a written test to measure students' critical thinking skills. The results showed that students had good mathematical critical thinking skills. Overall, students can investigate the context of the problem (interpretation), model or formulate mathematical problems (analysis), develop answer concepts by applying appropriate strategies (evaluation), and write conclusions (inference). The results of the data analysis concluded that of the three students who took the test, S-1 had excellent critical thinking skills